Analysis of a Sedan Car Seat Vibration - Muhamad Rusydi Roslan; Gigih Priyandoko (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2019)
Ride comfort in vehicle transportation is quite complex, and it depends on various dynamic performance criteria and subjective perception from the car passengers. Vibration discomfort from various factors such as vehicle conditions, the speed of the vehicle, road surface condition, vehicle load, and operating condition can lead to poor ride comfort. Driver seat will be the main part of a car that needed to get a dynamic comfort. Comfort and safety are major factors that need to be considered. To ensure the safety for passenger, the driver must feel comfortable while driving. The objective of this project is to analyze the vibration at the seat of a Proton Wira at different speeds, different loads and different road surfaces. In this project, use six different speeds. Vibration data from two types of road and three different loads are collected using two accelerometers sensor that place on driver seat and seat frame. The rough surface will cause a car to generate more vibration. The results for frequency and time responses show that the vibration increases at the dirt road.